Range size heritability in Carnivora is driven by geographic constraints - Machac, Antonin; Zrzavý, Jan; Storch, David (The American naturalist, 2011)
Range size heritability refers to an intriguing pattern where closely related species occupy geographic ranges of similar extent. Its existence may indicate selection on traits emergent only at the species level, with interesting consequences for evolutionary processes. We explore whether range size heritability may be attributable to the fact that range size is largely driven by the size of geographic domains (i.e., continents, biomes, areas given by species' climatic tolerance) that tend to be similar in phylogenetically related species. Using a well-resolved phylogeny of Carnivora, we show that range sizes are indeed constrained by geographic domains and that the phylogenetic signal in range sizes diminishes if the domain sizes are accounted for. Moreover, more detailed delimitation of species' geographic domain leads to a weaker signal in range size heritability, indicating the importance of definition of the null model against which the pattern is tested. Our findings do not reject the hypothesis of range size heritability but rather unravel its underlying mechanisms. Additional analyses imply that evolutionary conservatism in niche breadth delimits the species' geographic domain, which in turn shapes the species' range size. Range size heritability patterns thus emerge as a consequence of this interplay between evolutionary and geographic constraints.
Keywords: populační dynamika; Carnivora; druhová specificita; ekosystém; biologické modely; Animals; Ecosystem; Phylogeny; Population Dynamics; Models, Biological; zvířata; biologická evoluce; Biological Evolution; Geography; fylogeneze; Species Specificity; zeměpis